Abbreviation As Articulation: A Qualitative Linguistic Exploration Of Communicative Functions In Discord Chats - Silitonga, Sarah; Selviana Napitupulu (Jurnal Ilmu Pendidikan dan Sosial, 2026)
This paper investigates communicative purposes of the use of abbreviations in Discord chats based on the Computer-Mediated Discourse Analysis (CMDA) framework. Over three months, 500 chat messages in five Discord servers of gaming, educational and hobby communities were gathered. The study found four types of abbreviations, including initialisms (42%), phonological reductions (28%), Gen Z slang (22%), and alphanumeric replacements (8%). Results show that abbreviations have four main communicative purposes, namely, structural efficiency, tone modulation pragmatically, interactional continuity, and social identity construction. Abbreviations are multi-purpose resources that can only have sense in a context of negotiation, and at the same time they carry semantic, pragmatic, and social indexicalities. Such immense popularity of Gen Z forms like fr, ngl and no cap suggests that abbreviations have become sociolinguistic signifiers of belonging to a culture and generational identity. This paper has made a contribution to digital linguistics by enlightening on the influence of abbreviations in establishment of connotation and social bond within virtual communities.